Unraveling the impact of human cerebrospinal fluid on human neural stem cell fate - Radoszkiewicz, Klaudia; Bzinkowska, Aleksandra; Sypecka, Monika; Sulejczak, Dorota; Ferrari, Daniela; Gelati, Maurizio; Luigi Vescovi, Angelo; Sarnowska, Anna (Frontiers in Cell and Developmental Biology, 2025)
Human neural stem/progenitor cells (hNSCs) can potentially treat neurological diseases, but their low survival and proliferation rates after transplantation remain challenging. In our study, we preincubated hNSCs with the human cerebrospinal fluid (CSF) to obtain closer to the physiological brain environment and to assess NSC fate and their therapeutic abilities in vitro, ex vivo, and in vivo. We observed significant changes in the differentiation, migratory, and secretory potential of CSF-treated hNSCs, as well as their elevated neuroprotective potential after co-culture with ischemically damaged by oxygen-glucose deprivation (OGD) organotypic rat hippocampal slices culture (OHC) in comparison to the cells cultured in the standard conditions. Next, we investigated their survival and anti-inflammatory abilities in an in vivo ouabain-induced stroke model. This study highlighted and confirmed the critical importance of nutritional supplementation in maintaining NSC culture and enhancing its therapeutic properties.